Aplicación de títeres y socialización en niños de la Institución Educativa Inicial N° 351, Huanta Pevas 2021 - Meregildo Chichipe, Erika Milagros (2023)
This summary presents the results of the research whose main objective was to relate the application of puppets and socialization in children of the Initial Educational Institution No. 351 "Huanta", District of Pevas. The study's design and type of research were field, cross-sectional, bivariate, non-experimental, and relational, respectively. It had as a population 100 children from the educational institution, which in turn was the sample. For the collection of information data, a questionnaire and an information guide validated by experts in the field were used as instruments. The survey and observation technique were used. The conclusion is that since the student’s t statistic value = 7.884; p-value (bilateral significance) = 0.000 less than 0.05, so the Ho (null hypothesis) is rejected and the Ha (main hypothesis) is accepted with a significance level of 0.05, so it is tested the research hypothesis: "There is a significant relationship between the use of puppets and socialization in children of the initial educational institution No. 351 Huanta Pevas 2021"